HUBUNGAN PERAN PERAWAT DENGAN PELAKSANAAN PROMOSI KESEHATAN PADA PENDERITA HIPERTENSI - Mona Hastuti (Universitas Prima Indonesia, 2022)
Health promotion can influence a person in having knowledge and motivation about health sciences, including a healthy and regular way of life. The role of nurses who have received information or knowledge through health education can also have positive values, attitudes and motivations in carrying out matters relating to the maintenance, assistance, and treatment of hypertension. The objective of this study was to determine the effectiveness of the nurse's role in conducting health promotions for patients with hypertension. This type of research was an analytic survey with a cross sectional design. The population in this study were 42 people with hypertension in UPT Puskesmas Marike Kecamatan Kutambaru. The sampling technique in this study was determined by a total sampling technique of 42 people. The results of the chi square test based on the degree of significance (α) = 0.05 and df =1 obtained the calculation results, namely X²count 9.732 > X²table 3.841, it can be concluded that the value which means Ho is rejected Ha is accepted. The conclusion of the study is that there is a relationship between the nurse's roles with conducting health promotions for patients with hypertension. It is hoped that nurses will implement the health promotion program for hypertension sufferers better so that the symptoms and prevention of hypertension can be implemented properly.